2014
DOI: 10.1111/mbe.12057
|View full text |Cite
|
Sign up to set email alerts
|

School Schedules Affect Sleep Timing in Children and Contribute to Partial Sleep Deprivation

Abstract: Although the environmental light/dark cycle is the main zeitgeber for the human species, the social cues seem to be important in the synchronization of circadian rhythms. In Brazil, the existence of two school schedules-one with only morning classes (MG) and other with only afternoon classes (AG)-allows the investigation of the effect of school activities on light exposure and sleep/wake patterns in children. Forty-seven children wore wrist actimeters for a week for registration of light and sleep data. MG chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
2
13
0
2
Order By: Relevance
“…Therefore, the benefits of a late school start time (afternoon school shift) on sleep habits and circadian rhythms in adolescents have not been promoted in the country. The results of this study and previous studies (Anacleto et al ., ; Arrona‐Palacios et al ., ; Carissimi et al ., ; Natal et al ., ; Valdez et al ., 1996) may be used as examples of how a late school start time prevents adolescents from presenting sleep restriction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the benefits of a late school start time (afternoon school shift) on sleep habits and circadian rhythms in adolescents have not been promoted in the country. The results of this study and previous studies (Anacleto et al ., ; Arrona‐Palacios et al ., ; Carissimi et al ., ; Natal et al ., ; Valdez et al ., 1996) may be used as examples of how a late school start time prevents adolescents from presenting sleep restriction.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous double‐shift school system studies on sleep habits, morning shift students reported shorter sleep duration and daytime sleepiness and were exposed to bright light earlier than adolescents from the afternoon shift. In contrast, afternoon shift students reported longer times in bed and later rising times and bedtimes and were exposed to bright light later than morning shift students (Anacleto, Adamowicz, Simões da Costa Pinto, & Louzada, ; Arrona‐Palacios, García, & Valdez, ; Carissimi et al ., ; Natal et al ., ). Some studies have analysed the consequences of sleep habits when adolescents change from one school shift to another (e.g., from an afternoon shift to a morning shift).…”
Section: Introductionmentioning
confidence: 99%
“… 144) One hour of delay in school start time was significantly associated with enhancement of attention as well as improvements in cognitive performances in students. 145) Students attending morning classes suffered more from sleep restriction than did those attending afternoon classes, 146) and a Brazilian study demonstrated the influence of school start time on the sleeping habits of students. 147) Moreover, in another study, delaying the school start time not only improved the quality of sleep, but also ameliorated mood and behavioral symptoms in adolescents.…”
Section: Future Treatment Considerations For Sleep Problems In Adhdmentioning
confidence: 99%
“…Durante a adolescência, ocorrem diversas mudanças, tanto de origens biológicas e maturacionais quanto as de cunho comportamental, que contribuem para o atraso da fase do sono, a redução das horas de sono e o aumento da sonolência diurna 1,2 e que sofrem influência de fatores biopsicossociais 3 . Andrade et al 4 apontaram que mudanças do padrão de sono podem representar uma tendência ontogenética ao longo da puberdade.…”
Section: ▄ Introduçãounclassified
“…Andrade et al 4 apontaram que mudanças do padrão de sono podem representar uma tendência ontogenética ao longo da puberdade. Além disso, a redução da duração de sono se deve pela interação entre questões ontogênicas e sociais, por exemplo, início das aulas muito cedo, ocasionando, consequentemente, o aumento da sonolência diurna [1][2][3][4] .…”
Section: ▄ Introduçãounclassified